PENGARUH LAPORAN KEBERLANJUTAN DAN DIVERSITAS GENDER TERHADAP BIAYA UTANG (Sub Sektor Perusahaan Makanan dan Minuman yang Terdaftar di BEI Tahun 2018-2021) - Andri Syahputra; Tartila Devy (CV. Adiba Aisha Amira, 2023)
This research is a quantitative exploration which means finding out and investigating how much influence Sustainability Reports and Gender Diversity have on Costs. In this study, a sample of 43 companies included in the Food and Beverage subsector and listed on the Indonesia Stock Exchange (IDX) in the 2018-2021 period was used with the purposive sampling method used in sampling. This study also utilizes additional information obtained through the IDX website and company websites. data analysis was carried out using multiple linear regression methods, and hypothesis testing was carried out using the SPSS version 22 application. The first hypothesis shows that sustainability reports have an effect on debt costs with a significance weighted 0.024 <0.05, the second hypothesis shows gender diversity has an effect on debt costs with a significance weighted 0.003 <0.05, and the third hypothesis shows that sustainability reports and gender diversity have an effect on debt costs with a significance weighted 0.003 <0.05. From the test the coefficient of determination was found (R2) in a percentage of 0.001 or 0.1%, this indicates that the independent variables of sustainability reports and gender diversity have an effect of 0.1% on the cost of debt, the remaining 99.9% is influenced by other variables.